1995
DOI: 10.1172/jci118088
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of mdr-1 expression by 8-Cl-cAMP in multidrug resistant MCF-7 human breast cancer cells.

Abstract: 8-Cl-cAMP, a site-selective analogue of cAMP, decreased mdr-1 expression in multidrug-resistant human breast cancer cells. A sixfold reduction of mdr-1 mRNA expression by 8-Cl-cAMP began within 8 h of treatment and was associated with a decrease in the synthesis of P-glycoprotein and with an increase in vinblastine accumulation. A reduction in mdr-1 expression after 8-Cl-cAMP treatment was also observed in multidrug-resistant human ovarian cancer cell lines. 8-Cl-cAMP is known to change the ratio between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…In particular, it has been suggested that PKA induced phosphorylation of Raf-1 reducing its ability to bind Ras and then blocking the ERKs signalling (Wu et al, 1993). However, 8-Cl-cAMP is not considered an activator of PKA, conversely it is rather an antagonist of PKA-I (Rohlff et al, 1993;Cho-Chung et al, 1995;Scala et al, 1995) which is the major isoenzyme expressed in KB cells (Budillon et al, unpublished observation). In addition, we have demonstrated that 8-Cl-cAMP had no effect on Raf-1 kinase activity in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it has been suggested that PKA induced phosphorylation of Raf-1 reducing its ability to bind Ras and then blocking the ERKs signalling (Wu et al, 1993). However, 8-Cl-cAMP is not considered an activator of PKA, conversely it is rather an antagonist of PKA-I (Rohlff et al, 1993;Cho-Chung et al, 1995;Scala et al, 1995) which is the major isoenzyme expressed in KB cells (Budillon et al, unpublished observation). In addition, we have demonstrated that 8-Cl-cAMP had no effect on Raf-1 kinase activity in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…PKA-I is overexpressed in tumour cells and is increased in normal cells upon exposure to mitogenic stimuli (Miller et al, 1993;Tortora et al, 1993;Cho-Chung et al, 1995), whereas PKA-II expression is typical of terminally differentiated tissues and growth-arrested cells (Schwartz and Rubin, 1985;Cho-Chung et al, 1995). 8-Cl-cAMP treatment of tumour cells reduces PKA-I activity and concomitantly increases PKA-II activity (Rohlff et al, 1993;Budillon et al, 1995;Cho-Chung et al, 1995;Scala et al, 1995). Therefore, the catalytic activity of PKA may be affected by 8-Cl-cAMP through regulation of the expression of the two isoenzymes rather than by direct activation, as previously demonstrated (Scala et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However 8-Cl-cAMP does not affect the doxorubicin sensitivity of MDR-expressing cell lines (Borsellino et al, 1994), although it is able to down-regulate the expression of MDR (Glazer and Rohlff, 1994;Scala et al, 1995).…”
mentioning
confidence: 85%
“…Mutations between -61 and -43 resulted in a 6-fold decrease in promoter activity when the mutant MDR1 promoter construct was transiently transfected into KB-8-5 cells, and SP1 was shown to activate the MDR1 promoter when co-transfected into Drosophila cells (Cornwell, 1993a). In addition, the activity of the SP1 phosphoprotein is regulated by protein kinase A, and it has been suggested that the down-regulation of MDR1 by the PKA inhibitor 8-Cl-cAMP (Scala, 1995;Rohlff, 1995) is mediated by SP1 (Rohlff, 1998). Although initially proposed to be a critical factor for the basal transcription of MDR1 in all cells, recent evidence suggests that this requirement may be cellspecific, since mutation of this element in several human neuroblastoma cell lines had only a small effect on basal transcription (Thayer, S. and Scotto, K., unpublished).…”
Section: Constitutive Regulatorsmentioning
confidence: 99%